Groundwater Governance in the United States: Common Priorities and Challenges. Issue 5 (18th November 2014) - Megdal, Sharon B.; Gerlak, Andrea K.; Varady, Robert G.; Huang, Ling‐Yee
Abstract Groundwater is a critical component of the water supply for agriculture, urban areas, industry, and ecosystems, but managing it is a challenge because groundwater is difficult to map, quantify, and evaluate. Until recently, study and assessment of governance of this water resource has been largely neglected. A survey was developed to query state agency officials about the extent and scope of groundwater use, groundwater laws and regulations, and groundwater tools and strategies. Survey responses revealed key findings: states' legal frameworks for groundwater differ widely in recognizing the hydrologic connection between surface water and groundwater, the needs of groundwater‐dependent ecosystems, and the protection of groundwater quality; states reported a range in capacity to enforce groundwater responsibilities; and states have also experienced substantial changes in groundwater governance in the past few decades. Overall, groundwater governance across the United States is fragmented. States nevertheless identified three common priorities for groundwater governance: water quality and contamination, conflicts between users, and declining groundwater levels. This survey represents an initial step in a broader, continuing effort to characterize groundwater governance practices in the United States.